Managing Nutrition Impact Symptoms in Cancer Cachexia: A Case Series and Mini Review - Khorasanchi, Adam; Nemani, Srinidhi; Pandey, Sudeep; Del Fabbro, Egidio (Frontiers in Nutrition, 2022)
Abstract Malnutrition is common in cancer patients and can occur throughout a patient’s disease course. The contributors to the clinical syndrome of Cancer Cachexia are often multifactorial, and produced by the cancer and associated pro-inflammatory response. Since cancer cachexia is a "multifactorial syndrome", a multimodal therapeutic approach is ideal. A key component of therapy is identifying and managing symptom barriers to adequate oral intake, known as nutritional impact symptoms (NIS).NIS are associated with reduced intake and weight loss in patients with advanced cancer, and aggregate NIS are a predictor of survival in patients with Head and Neck Cancer and in selected patients undergoing surgery for esophageal cancer. Currently, there are no guidelines regarding the specific management of NIS in oncology patients. Experience from specialist centers suggest relatively simple assessments and inexpensive interventions are available for the diagnosis and treatment of NIS. We present three patient cases from a cachexia clinic, where NIS management decreased symptom burden and improved clinical outcomes such as weight and physical performance.